Design And Hydrodynamic Performance Analysis of a Marine Water Jet Using SolidWorks and CFD Simulation - Abdulhafiz Younis Mokhtar; Madi Abdullah Naser; Ahmed Gaddour; Nuri M. Eshoul (African Journal of Advanced Pure and Applied Sciences, 2025)
Marine water jet propulsion systems require optimized nozzle and duct geometries to maximize thrust and efficiency, yet design improvements are often limited by the lack of integrated hydrodynamic analysis. This study aimed to design an efficient marine water jet and evaluate its hydrodynamic performance through combined CAD modeling and CFD simulation. A three-dimensional model of the propulsion system was developed in SolidWorks, incorporating optimized nozzle and internal duct geometry. Computational Fluid Dynamics (CFD) simulations were performed to analyze velocity fields, pressure distributions, and thrust output under defined fluid properties and boundary conditions. Both the complete jet system (including a free-surface water interface) and a simplified nozzle-only configuration was examined. Simulations revealed clear correlations between geometric parameters and performance, identifying configurations that improved energy conversion and reduced wall friction. The optimized design achieved higher thrust efficiency compared to baseline geometries. Integrated CAD–CFD analysis provides a robust framework for marine water jet design, enabling targeted geometry refinements that enhance hydrodynamic performance. The findings support future development of high-efficiency propulsion systems for marine applications.